2013
DOI: 10.1080/10615806.2013.839989
|View full text |Cite
|
Sign up to set email alerts
|

Predicting performance and performance satisfaction: mindfulness and beliefs about the ability to deal with social barriers in sport

Abstract: This research investigates the role of beliefs about the ability to deal with specific social barriers and its relationships to mindfulness, football performance, and satisfaction with one's own and team performance. Study 1 aimed at eliciting these social barriers. Study 2 tested (i) whether self-efficacy referring to social barriers would predict performance over and above task-related self-efficacy and collective efficacy and (ii) the mediating role of self-efficacy to overcome social barriers in the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
2
27
0
4
Order By: Relevance
“…These weak 19 SHORT MINDFULNESS MEASURE correlations raise doubts about the predictive utility of self-reported mindfulness. These data are consistent with previous studies that found weak positive correlations of mindfulness with performance (r = .17, Blecharz et al, 2014;r = .33, Röthlin et al, 2016;r = .19, Sarnell, 2012). All three of these studies used general mindfulness measures rather than those specifically assessing mindfulness in sporting contexts.…”
Section: Reliability and Validity Of Shortened Measuressupporting
confidence: 93%
See 2 more Smart Citations
“…These weak 19 SHORT MINDFULNESS MEASURE correlations raise doubts about the predictive utility of self-reported mindfulness. These data are consistent with previous studies that found weak positive correlations of mindfulness with performance (r = .17, Blecharz et al, 2014;r = .33, Röthlin et al, 2016;r = .19, Sarnell, 2012). All three of these studies used general mindfulness measures rather than those specifically assessing mindfulness in sporting contexts.…”
Section: Reliability and Validity Of Shortened Measuressupporting
confidence: 93%
“…In previous studies, mindfulness has been shown to be associated with better performance (Blecharz et al, 2014;Röthlin, Horvath, Birrer, & Holtforth, 2016), lower anxiety (Röthlin et al, 2016), higher flow (Cathcart, McGregor, & Groundwater, 2014;Kaufman, Glass, & Arnkoff, 2009;Kee & Wang, 2008;Pineau, Glass, Kaufman, & Bernal, 2014), higher self-efficacy (Blecharz et al, 2014), fewer intrusive thoughts (Thienot et al, 2014), and less attachment to those thoughts (Zhang, Chung, Si, & Gucciardi, 2016).…”
Section: Mindfulness In Athletesmentioning
confidence: 93%
See 1 more Smart Citation
“…Accordingly, self-efficacy is a critical factor for the change of behavior and is considered a self-control mechanism, managing the motivation and actions of human beings [49]. Besides, an individual's self-efficacy can prevent the negative effects of stress [50] and it influences personal work attitudes such as interests, goals, and behaviors in the working field [51]. However, most research about self-efficacy has been focused on the education domain over the last two decades [52][53][54][55].…”
Section: Self-efficacymentioning
confidence: 99%
“…Satisfaction with skills and actions is one of the key aspects of subjective well‐being (Diener, Oishi, & Lucas, ). Satisfaction in sports refers to the affective aspect of well‐being (Nicholls, Polman, & Levy, ) and it may be directly or indirectly influenced by various types of self‐efficacy (Blecharz et al., ). The present research focuses on satisfaction with performance and skills (SPS), defined as athletes’ satisfaction with their personal level of play, sport skills, and competition outcomes as well as athletes’ satisfaction with their team's levels of play and competition outcomes (Balaguer, Duda, Atienza, & Mayo, ).…”
Section: Introductionmentioning
confidence: 99%